Элементы матричной алгебры в Ms Excel - Листопад, Владимир Васильевич (My University, 2020)
В статье рассмотрены отдельные случаи применения пакета Ms Excel в процессе обучения высшей математике, в частности, поиск обратной матрицы согласно определения и методом преобразований (метод Жордана-Гаусса). Решение системы линейных уравнений (СЛР) выполнено матричным методом (два действия) и методом преобразований (Жордана-Гаусса). The article considers some cases of application of the Ms Excel package in the process of teaching higher mathematics, in particular, the construction of an inverse matrix according to the definition and the method of transformations (Jordan-Gauss method). Solving systems of linear equations (SLR) - performed by the matrix method (in two steps) and the transformation method (Jordan-Gauss).
Keywords: матрица; метод Жордана-Гаусса; системы линейных уравнений; обратная матрица; matrix; inverse matrix; systems of linear equations; Jordan-Gauss method; кафедра вищої математики імені проф. Можара В. І.